Nanoparticle based on W-VO2-x-coated AA core-shell structure, preparation method of nanoparticle and thermochromic intelligent window
By forming oxygen vacancies on the surface of vanadium dioxide nanoparticles and forming a core-shell structure with ascorbic acid, the problems of insufficient visible light transmittance and solar energy modulation ability of thermochromic smart window materials at low phase transition temperatures were solved, high-performance thermochromic performance was achieved, and the application of thermochromic smart windows and radiative cooling was promoted.
Patent Information
- Application Number
- CN202510826248.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-10-03
AI Technical Summary
Existing thermochromic smart window materials cannot effectively improve visible light transmittance and solar energy modulation capability at the same time at low phase change temperatures. Element doping leads to performance degradation, and the multi-layer film structure cannot meet the needs of actual applications.
Using W-VO2-x@AA core-shell structured nanoparticles, oxygen vacancies are formed on the surface of tungsten-doped vanadium dioxide nanoparticles, and a composite layer is formed with ascorbic acid. The optical modulation is enhanced by oxygen vacancy regulation and localized surface plasmon resonance absorption to prepare an anti-reflection layer with a refractive index gradient.
The solar modulation efficiency is significantly improved at low phase change temperature while maintaining a high visible light transmittance, which weakens the antagonistic effect between visible light transmittance and solar modulation efficiency and promotes the development of thermochromic smart windows and radiative cooling.
Smart Images

Figure CN120737653A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of architectural glass and its coating materials, and specifically relates to a W-VO based 2-x @AA core-shell structured nanoparticles, their preparation method, and their application in thermochromic smart windows. Background Art
[0002] The energy consumption of building operation accounts for more than 20% of the total energy consumption of social operation, which is used to meet daily energy needs such as indoor lighting, air conditioning, ventilation and heating. Windows are an indispensable component of the building envelope, and their main functions include providing views, light transmission and ventilation. Compared with other building maintenance parts, the high thermal emissivity and low thermal regulation performance of glass in windows result in a large amount of energy loss. Therefore, by improving the thermal and optical properties of glass windows, it is possible to reduce heat loss and reduce heating and cooling energy consumption, playing an important role in reducing building energy demand and helping to achieve the country's "dual carbon" goals. The development method of high-performance adjustable radiant cooling thermochromic smart windows has become an urgent problem to be solved.
[0003] Vanadium dioxide (VO2) is a transition metal semiconductor material with semiconductor metal phase transition characteristics. When the temperature is higher than the phase transition temperature (T c ), VO2 will undergo a transition from semiconductor phase (M phase) to metallic phase (R phase), and its optical properties will undergo a sudden change. This transition is reversible. Therefore, VO2 has broad application prospects in thermochromic smart windows. In the research of VO2 thermochromic smart windows, how to improve the visible light transmittance (T lum ), solar modulation capability (△T sol) has become a major obstacle to its application in thermochromic smart windows. Researchers have developed various methods to enhance its thermochromic performance, including element doping, core-shell structures, and multilayer film structures. Element doping involves incorporating elements (such as tungsten, hydrogen, zirconium, magnesium, hafnium, and tantalum) into the vanadium dioxide preparation process. These elements occupy or influence the positions of V and O atoms, disrupting or distorting the V–V chains in the monoclinic structure, reducing the orbital splitting gap, and enhancing the VO₂ electron concentration, thereby reducing the thermal driving force for electron motion. Tungsten doping lowers the phase transition temperature of VO₂ to 48°C, which is highly consistent with practical needs. However, element doping often reduces the thermochromic performance of smart windows. While the phase transition temperature is lowered, the visible light transmittance and solar energy modulation efficiency decrease, making them unsuitable for practical applications. Visible light transmittance and solar energy modulation efficiency are equally important for thermochromic smart windows. Researchers have proposed using micro- and nanostructured designs to address this performance improvement. These approaches can be categorized into hybrid, core-shell, and multilayer film structures, depending on the structure. By preparing core-shell nanoparticles, localized surface plasmon resonance absorption can be used to enhance the optical modulation depth and change the wavelength of the absorption peak, but this often results in a lower T lum The multilayer film structure adds an anti-reflection layer based on the principle of refractive index gradient, which can improve T to a certain extent. lum However, it often leads to the problem of insufficient solar energy regulation ability and fails to meet the requirements of effectively regulating room temperature.
[0004] Ascorbic acid (AA), a bioactive organic compound, has been used by researchers to achieve hydrogen doping of W-VO2 with a low phase transition temperature. AA can form a surface coordination effect with W-VO2 nanoparticles. Due to the unique dienol structure of ascorbic acid and the doping defects of W, it can inject electrons into the W-VO2 lattice through the formed COV bonds, thereby increasing the carrier density within VO2. In existing studies, researchers often use AA to lower the phase transition temperature of VO2 and enhance its acid resistance and antioxidant properties. At the same time, AA can also be used to continuously improve the visible light transmittance and solar modulation capability of W-VO2 through the mechanism of refractive index gradient and localized surface plasmon resonance absorption enhancement. Summary of the Invention
[0005] In view of the problem that the dimming devices based on vanadium dioxide nanoparticle materials currently used in microelectronics fields such as smart windows and radiative cooling cannot effectively improve the visible light transmittance and solar energy modulation ability at the same time, the present invention provides a W-VO 2-x @AA core-shell structured nanoparticles and their preparation method and thermochromic smart window, based on oxygen vacancy regulation, greatly improve W-VO 2-x / PVP thermochromic smart window maintains a high visible light transmittance while improving the solar modulation rate, weakening or even breaking the antagonism between the two optical properties of visible light transmittance and solar modulation efficiency, further promoting the application progress of vanadium dioxide in thermochromic smart windows and radiative cooling.
[0006] According to one aspect of the present invention, a W-VO based 2-x @AA core-shell structured nanoparticles are prepared by the following method:
[0007] S1. The W-VO2 nanoparticles are subjected to vacuum heat treatment to form oxygen vacancies on the surface of the tungsten-doped vanadium dioxide nanoparticles to obtain W-VO2 nanoparticles containing oxygen vacancies. 2-x nanoparticles (x represents oxygen vacancies).
[0008] S2. Add ascorbic acid powder to a deionized water solution containing glacial acetic acid to form a precursor solution, and stir at room temperature to fully dissolve the precursor solution;
[0009] S3, add W-VO containing oxygen vacancies obtained in S1 to the solution obtained in S2 2-x Nanoparticles, ultrasonic dispersion makes W-VO 2-x The nanoparticles are uniformly dispersed in the precursor solution;
[0010] S4. The suspension obtained in S3 is reacted at 80-90° C. for 8-10 hours. After the reaction is completed, it is washed several times, and then the sample is centrifuged and dried.
[0011] According to another aspect of the present invention, a W-VO based 2-x The method for preparing nanoparticles with an AA core-shell structure comprises the following steps:
[0012] S1. The W-VO2 nanoparticles are subjected to vacuum heat treatment to form oxygen vacancies on the surface of the tungsten-doped vanadium dioxide nanoparticles to obtain W-VO2 nanoparticles containing oxygen vacancies. 2-x nanoparticles (x represents oxygen vacancies).
[0013] S2. Add ascorbic acid powder to a deionized water solution containing glacial acetic acid to form a precursor solution, and stir at room temperature to fully dissolve the precursor solution;
[0014] S3, add W-VO containing oxygen vacancies obtained in S1 to the solution obtained in S2 2-x Nanoparticles, ultrasonic dispersion makes W-VO 2-x The nanoparticles are uniformly dispersed in the precursor solution;
[0015] S4. The suspension obtained in S3 is reacted at 80-90° C. for 8-10 hours. After the reaction is completed, it is washed several times, and then the sample is centrifuged and dried.
[0016] In the above W-VO 2-x @AA core-shell structured nanoparticles and their preparation method:
[0017] Preferably, in S1: the temperature of the vacuum heat treatment is 300-450° C., and the time is 30-60 min.
[0018] Preferably, in S2: the molar ratio of glacial acetic acid to ascorbic acid in the precursor solution is 7:1.
[0019] Preferably, in S3: W-VO 2-x The molar ratio of nanoparticles to ascorbic acid was 1:4.
[0020] Preferably, in S3: after the reaction is completed, washing is performed with deionized water and anhydrous ethanol for multiple times.
[0021] According to another aspect of the present invention, a thermochromic smart window is provided, which is composed of the W-VO based 2-x @AA core-shell structured nanoparticles were prepared.
[0022] Furthermore, the preparation of the thermochromic smart window includes the following steps:
[0023] (1) The W-VO based 2-x The AA core-shell nanoparticles and PVP were added to anhydrous ethanol and ultrasonically vibrated, then magnetically stirred to ensure uniform distribution and then allowed to stand for later use.
[0024] (2) Apply the supernatant of the suspension obtained in step (1) to the surface of the pretreated glass substrate to obtain W-VO 2-x @AA-based thermochromic smart window.
[0025] Preferably, the W-VO based 2-x The mass ratio of @AA core-shell structured nanoparticles to PVP is 1:30.
[0026] Preferably, the pretreatment in step (2) includes: firstly, placing the glass substrate in an acetone solution for ultrasonic cleaning, then placing it in anhydrous ethanol for ultrasonic cleaning, and finally placing it in deionized water for ultrasonic cleaning, and drying it for use.
[0027] Preferably, the coating in step (2) includes: first dropping the supernatant of the suspension obtained in step (1) onto the surface of the pretreated glass substrate, then using a spin coater to spin coat, first rotating at a low speed, then at a high speed, and finally drying for use.
[0028] The beneficial effects of the present invention are:
[0029] W-VO of the present invention 2-x @AA core-shell structured nanoparticles provide a composite layered structure regulated by oxygen vacancies. On the one hand, in the W-VO 2-x AA acid organic core-shell structure is formed on the surface of nanoparticles. Since the refractive index of AA acid is lower than that of W-VO containing oxygen vacancies, 2-x The refractive index of the nanoparticles is higher than that of the PVP layer. Therefore, the three-layer structure forms a refractive index gradient, which can be used as an anti-reflection layer to reduce the visible light oxygen vacancy W-VO 2-x The reflectivity of the nanoparticles can improve the transmittance of the entire structure to visible light; due to the unique dienol structure of ascorbic acid, it can be combined with W-VO containing oxygen vacancies. 2-x Forming a link bond, injecting electrons into the W-VO containing oxygen vacancies through the formed COV bond 2-x inside the lattice, thereby increasing W-VO 2-x The internal carrier density makes the overall structure have a greater shielding effect on near-infrared light in the solar band.
[0030] Based on this, the present invention prepares W-VO with all-round high performance oxygen vacancy regulation that is more suitable for practical applications. 2-x @AA / PVP thermochromic smart window greatly improves W-VO at low phase transition temperature 2-x The PVP thermochromic smart window achieves high solar modulation efficiency while maintaining high visible light transmittance, weakening or even breaking the antagonistic relationship between visible light transmittance and solar modulation efficiency, further promoting the development of VO2 thermochromic smart windows and radiative cooling. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 W-VO of Examples 1-6 of the present invention 2-x @AA Flowchart for the preparation of nanoparticle-based thermochromic smart window samples.
[0032] Figure 2 W-VO prepared in Examples 1-6 of the present invention 2-x @AA Visible-mid-infrared infrared spectra of nanoparticle-based thermochromic smart window samples; (a) shows the transmittance of different samples in the 380-2500nm band; (b) Based on the data obtained by the spectrophotometer, the visible light transmittance and solar energy regulation efficiency of different samples were calculated and statistically analyzed.
[0033] Figure 3 W-VO prepared in Examples 1-6 of the present invention 2-x@AA Diagram of the control principle of nanoparticle-based thermochromic smart window sample.
[0034] Figure 4 W-VO prepared in Example 1 of the present invention 2-x @AA Scanning electron microscope image of a nanoparticle-based thermochromic smart window sample.
[0035] Figure 5 W-VO prepared in Example 1 of the present invention 2-x @AA Actual photo of the nanoparticle-based thermochromic smart window sample. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments and accompanying drawings.
[0037] like Figure 1 As shown, the present invention provides a W-VO controlled by oxygen vacancy regulation. 2-x @AA core-shell structured nanoparticles and their preparation method, successfully designed and prepared oxygen vacancy-regulated W-VO on transparent glass through the refractive index gradient and LSPR resonance absorption enhancement principle. 2-x @AA core-shell structure model effectively prepared a radiative cooling thermochromic smart window, providing a higher visible light transmittance and improving its ability to modulate thermal radiation and near-infrared regulation.
[0038] Example 1
[0039] The specific steps of its preparation are as follows:
[0040] Step 1: Preparation before synthesis
[0041] A1: Cleaning experimental equipment and substrates
[0042] Ultrasonic cleaning was performed on the beaker, spoon, glass substrate, and magnet to ensure surface cleanliness. The substrate cleaning process was as follows: an appropriate amount of anhydrous ethanol was poured into the beaker and ultrasonically cleaned for 15 minutes to remove any impurities or dust. The substrate was then placed in a clean beaker and ultrasonically cleaned for 15 minutes each in acetone and anhydrous ethanol. Finally, the cleaned substrate was removed, transferred to a tray, and dried in an oven for 15 minutes.
[0043] A2: Weigh ascorbic acid powder, PVP powder, and oxygen vacancy-free W-VO2 nanoparticles
[0044] Use a high-precision electronic scale to weigh 4.403 g of ascorbic acid powder, 500 mg of W-VO2 nanoparticles, and 600 mg of PVP powder, and use a measuring cylinder to measure 10 ml of glacial acetic acid and 25 ml of deionized water, respectively.
[0045] Step 2: Oxygen vacancy regulation of W-VO 2-x Preparation of nanoparticles
[0046] 500 mg of oxygen vacancy-free W-VO2 nanoparticles were placed in a vacuum thermal annealing furnace and vacuum-heat-treated at 400 °C for 30 min to prepare W-VO2 nanoparticles containing oxygen vacancies. 2-x Nanoparticles;
[0047] Step 3: Oxygen vacancy regulation of W-VO 2-x Preparation of @AA core-shell structure:
[0048] A1: Prepare glacial acetic acid mixed solution
[0049] Dissolve 10 ml of glacial acetic acid in 25 ml of deionized water and stir at 30° C. for 30 minutes to prepare a mixed solution.
[0050] A2: Preparation of precursor solution
[0051] Add 4.403 g of ascorbic acid powder to the mixed solution and stir at 25-40°C to fully dissolve it to form a precursor solution;
[0052] A3: Preparation of W-VO 2-x @AA core-shell structure
[0053] Adding an appropriate amount of W-VO containing oxygen vacancies 2-x Nanoparticles are ultrasonically dispersed at 25-40°C to make the nanoparticles uniformly dispersed. The prepared suspension is placed in a thermostat and kept warm at 60-90°C for 6-10 hours. After the reaction is completed, it is washed with deionized water and anhydrous ethanol several times and centrifuged to obtain a sample. The obtained sample is placed in a thermostat and kept warm at 60-70°C for 8-12 hours to obtain a black powder.
[0054] Step 4: Oxygen vacancy W-VO 2-x (NP)&PVP solution preparation:
[0055] A1: Take 3 ml of anhydrous ethanol:
[0056] 600 mg of PVP was added to 3 ml of anhydrous ethanol and ultrasonically dispersed at 40°C for 30 min to form a dispersion.
[0057] A2: Add W-VO containing vacancies 2-x @AA powder:
[0058] Add W-VO to the dispersion 2-x @AA Continue ultrasonic oscillation for 1 hour, finally stir with a magnetic stirrer for 4 hours, and then let it stand for 24 hours for use.
[0059] Step 3: Oxygen vacancy regulation of W-VO 2-x Preparation of @AA nanoparticle-based composite film layer:
[0060] A1: Spin coating composite layer
[0061] Use a pipette to measure 140 μL of W-VO containing oxygen vacancies. 2-x The AA(NP)&PVP solution was dropped onto a transparent glass substrate, and the spin coating parameters were adjusted to a low speed of 800 r / min for 10 s and a high speed of 2000 r / min for 20 s.
[0062] A2: Heating oxygen vacancies to regulate W-VO 2-x @AA nanoparticle-based composite layer
[0063] After spin coating, the composite layer was heated at 60° C. for 5 minutes to remove surface haze and dry the layer. The resulting sample was numbered TA400.
[0064] Example 2
[0065] According to the specific steps of Example 1, oxygen vacancy-controlled W-VO was prepared on a transparent glass substrate. 2-x @AA nanoparticle-based composite layer, the only difference is that the vacuum heat treatment temperature used in step 2 is 300 degrees Celsius, and the resulting sample is numbered TA300.
[0066] Example 3
[0067] According to the specific steps of Example 1, oxygen vacancy-controlled W-VO was prepared on a transparent glass substrate. 2-x @AA nanoparticle-based composite layer, the only difference is that the vacuum heat treatment temperature used in A1 in step 2 is 350 degrees Celsius, and the resulting sample is numbered TA350.
[0068] Example 4
[0069] According to the specific steps of Example 1, oxygen vacancy-controlled W-VO was prepared on a transparent glass substrate. 2-x @AA nanoparticle-based composite layer, the only difference is that the vacuum heat treatment temperature used in A1 in step 2 is 450 degrees Celsius, and the resulting sample is numbered TA450.
[0070] Example 5
[0071] An oxygen-vacancy-controlled W-VO2@AA nanoparticle-based composite layer was prepared on a transparent glass substrate according to the specific steps of Example 1, except that the W-VO2 nanoparticles were not vacuum-heat-treated in Step 2. The obtained sample was numbered TA0.
[0072] The thermochromic smart window samples (TA0, TA300, TA350, TA400, TA450) prepared in Examples 1 to 5 of the present invention were tested using an ultraviolet-near infrared-visible spectrophotometer at 25° C. and 80° C., respectively. Figure 2 Visible-mid-infrared infrared spectra of different samples; (a) shows the transmittance of different samples in the 380-2500nm band; (b) based on the data obtained by the spectrophotometer, the thermochromic properties of different samples are calculated and statistically analyzed.
[0073]
[0074] ΔT sol =T sol,c -T sol,h (3)
[0075] ΔT NIR =T NIR,c -T NIR,h (4)
[0076] ΔT lum =ΔT sol –ΔT NIR (5)
[0077] In formulas (1)-(5), T(λ) is the spectral transmittance at wavelength λ, is the light sensitivity-wavelength relationship function of the human eye, is the solar radiation energy distribution spectrum when the angle between the sun and the horizon is 37°, T lum is the visible light transmittance of the material at low temperature (T lum ,L) and visible light transmittance at high temperature (T lum ,H) average value, T sol ,L,T sol ,H are the solar spectrum transmittance at low temperature (25℃) and high temperature (80℃), ΔT sol is the solar modulation capability, ΔT NIR is the near-infrared modulation capability, ΔT lum Represents visible light modulation capability.
[0078] like Figure 2 As shown in the figure, when the vacuum heat treatment temperature is less than 450℃, as the vacuum heat treatment temperature increases, the solar modulation rate of the thin films made of TA300, TA350, TA400 and TA450 samples increases significantly, but the visible light transmittance decreases slightly. This indicates that as the vacuum heat treatment temperature increases, the samples obtained after heat treatment react with AA in the hydrothermal reaction, and AA will turn to W-VO 2-x The injection of more electrons also leads to the blue shift of the LSPR absorption peak in the metallic state and the enhancement of the near-infrared light absorption.
[0079] Compared with TA0, the visible light transmittance of the film made of the TA400 sample decreased from 72.3% to 67%, a decrease of 7.33%, and the solar modulation rate increased from 9.23% to 12.1%, a performance improvement of 31.09%. This is due to the increase in electron density caused by oxygen vacancies, which affects the electron absorption of sunlight; on the other hand, the oxygen vacancies promote the coordination effect of surface molecules, resulting in more AA adsorption on the W-VO2 surface and more electron injection into the W-VO2. 2-x inside the lattice, thereby increasing the TA400 sample's ability to absorb near-infrared light.
[0080] Figure 3 The reaction mechanism of the present invention is described. It can be seen that when the vacuum heat treatment temperature is 300-450℃, a certain amount of oxygen vacancies can be generated inside the W-VO2 lattice. The oxygen vacancies generated by thermal excitation will reduce the binding energy of the VO bond, resulting in the loss of O atoms and the appearance of dangling bonds in the V atoms, which is conducive to the surface molecular coordination effect of the V atoms and AA. Therefore, in the W-VO 2-x More AA molecules will be chemically adsorbed on the surface of the nanoparticles and more electrons will be injected, eventually forming W-VO with thicker AA shell and higher electron density. 2-x @AA composite structure.
[0081] Figure 4 The images of the samples prepared in Examples 1-5 were taken by field emission scanning electron microscopy (SEM). Figure 4 W-VO as the core can be clearly observed in 2-x and AA shells. AA is darker in color due to its larger atomic number.
[0082] Figure 5 The W-VO of TA0, TA400 and TA450 samples prepared by spin coating on transparent glass substrate 2-x @AA / PVP smart window cross section and surface diagram. Figure 5 It can be seen from the figure that the formed smart window has a clear interface and a smooth surface.
[0083] It can be seen that the present invention provides a W-VO based 2-x @AA core-shell structured nanoparticles and their preparation method can be effectively applied to radiative cooling smart windows. Their spectral characteristics have been characterized, and their ability to modulate thermal radiation and near-infrared regulation has been improved, meeting the performance requirements of smart windows and radiative cooling. The process is simple and the preparation cost is reduced, thus promoting the development of microelectronic devices.
[0084] The technical solutions disclosed and proposed by the present invention can be implemented by those skilled in the art by drawing on the content of this document and appropriately changing the conditions, routes, and other aspects. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, it is obvious that those skilled in the art can modify or recombine the methods and technical routes described herein without departing from the content, spirit, and scope of the present invention to achieve the ultimate preparation technology. It is particularly important to point out that all similar substitutions and modifications that are obvious to those skilled in the art are considered to be included in the spirit, scope, and content of the present invention.
Claims
1. A novel W-VO based on oxygen vacancy regulation 2-x The method for preparing nanoparticles with a @AA core-shell structure is characterized in that: The steps include: S1. The W-VO2 nanoparticles are subjected to vacuum heat treatment to form oxygen vacancies on the surface of the tungsten-doped vanadium dioxide nanoparticles to obtain W-VO2 nanoparticles containing oxygen vacancies. 2-x Nanoparticles. S2. Add ascorbic acid powder to a deionized water solution containing glacial acetic acid to form a precursor solution, and stir at room temperature to fully dissolve the precursor solution; S3, add W-VO containing oxygen vacancies obtained in S1 to the solution obtained in S2 2-x Nanoparticles, ultrasonic dispersion makes W-VO 2-x The nanoparticles are uniformly dispersed in the precursor solution; S4. The suspension obtained in S3 is reacted at 80-90° C. for 8-10 hours. After the reaction is completed, it is washed several times, and then the sample is centrifuged and dried.
2. A W-VO based method according to claim 1 2-x The method for preparing nanoparticles with a @AA core-shell structure is characterized in that: In S1: the temperature of the vacuum heat treatment is 300-450° C., and the time is 30-60 min.
3. A W-VO based method according to claim 1 2-x The method for preparing nanoparticles with a @AA core-shell structure is characterized in that: In S2: the molar ratio of glacial acetic acid to ascorbic acid in the precursor solution is 7:
1.
4. A W-VO based method according to claim 1 2-x The method for preparing nanoparticles with a @AA core-shell structure is characterized in that: In S3: W-VO 2-x The molar ratio of nanoparticles to ascorbic acid was 1:
4.
5. A W-VO based 2-x @AA core-shell structured nanoparticles, characterized in that The method is as described in any one of claims 1 to 4.
6. A thermochromic smart window, characterized in that: Adopting a W-VO based method as claimed in claim 5 2-x @AA core-shell structured nanoparticles were prepared.
7. The thermochromic smart window according to claim 6, characterized in that: The preparation method comprises the following steps: (1) The W-VO based 2-x The AA core-shell nanoparticles and PVP were added to anhydrous ethanol and ultrasonically vibrated, then magnetically stirred to ensure uniform distribution and then allowed to stand for later use. (2) Apply the supernatant of the suspension obtained in step (1) to the surface of the pretreated glass substrate to obtain W-VO 2-x @AA-based thermochromic smart window.
8. The thermochromic smart window according to claim 7, characterized in that: Based on W-VO in step (1) 2-x The mass ratio of @AA core-shell structured nanoparticles to PVP is 1:
30.
9. The thermochromic smart window according to claim 7, characterized in that: The pretreatment in step (2) includes: firstly, placing the glass substrate in an acetone solution for ultrasonic cleaning, then placing it in anhydrous ethanol for ultrasonic cleaning, and finally placing it in deionized water for ultrasonic cleaning, and drying it for use.
10. The thermochromic smart window according to claim 7, characterized in that: The coating in step (2) includes: first dropping the supernatant of the suspension obtained in step (1) on the surface of the pretreated glass substrate, then using a spin coater to spin, first at low speed, then at high speed, and finally drying for use.